2017
DOI: 10.1002/er.3928
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of the performance of thermoelectric module with polydimethylsiloxane encapsulation

Abstract: Summary This paper presents a 2‐dimensional finite volume model to investigate the performance of thermoelectric module (TEM) with polydimethylsiloxane (PDMS) encapsulation. The voltage and temperature distributions of the TEM under 2 kinds of boundary conditions (constant cold‐side temperature and fixed convection heat transfer coefficient) are studied. To validate the developed model, 2 TEMs with or without PDMS encapsulation are fabricated, and the experimental tests are carried out. Both model predicted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The PDMS has been widely used in encapsulation processes for electronic devices owing to its excellent optical, mechanical, chemical, and biological properties. [ 42–44 ] Figure a presents the photograph (top) and exploded view illustration (bottom) of the PDMS encapsulated UVA sensor based on pRGO paper. Further detailed fabrication processes are detailed in the Experimental Section and the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The PDMS has been widely used in encapsulation processes for electronic devices owing to its excellent optical, mechanical, chemical, and biological properties. [ 42–44 ] Figure a presents the photograph (top) and exploded view illustration (bottom) of the PDMS encapsulated UVA sensor based on pRGO paper. Further detailed fabrication processes are detailed in the Experimental Section and the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…[191][192][193] Finally, several groups used integrated rigid thermoelectric legs in a flexible platform to create flexible devices. [176,[194][195][196][197][198][199][200][201][202][203] Flexible TEGs relying on the deposition of thin-film materials on flexible substrates are not stretchable since the deposited materials are rigid in nature, but can be flexible if they are thin enough. Additionally, in most cases, the temperature difference across the thin-film thermoelectric materials is small (if the heat flows through the thickness of the material), which results in low open-circuit voltage.…”
Section: Design Approachesmentioning
confidence: 99%
“…Since then, several studies reported various flexible TEGs incorporating rigid thermoelectric blocks. [176,[194][195][196][197][198][199][200][201][202][203] Such blocks can be interconnected using thin Cu traces. [200] Importantly, the space between the thermoelectric blocks should be electrically and thermally insulating; the latter helps to force heat to travel through the thermoelectric materials.…”
Section: Flexible Tegs Using Rigid Bulk Materialsmentioning
confidence: 99%
“…PDMS is a silicon-based organic polymer that behaves as an inert, non-toxic, non-flammable, optically transparent elastomer with low thermal conductivity [39,40]. The thickness, shape, or size of the PDMS layer can be easily controlled.…”
Section: Te Fiber Sensorsmentioning
confidence: 99%